2021
DOI: 10.1002/jor.25124
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the patellar tendon moment arm identified with an improved measurement framework

Abstract: The mechanical advantage of the knee extensor mechanism depends heavily on the patellar tendon moment arm (PTMA). Understanding which factors contribute to its variation may help improve functional outcomes following arthroplasty. This study optimized PTMA measurement, allowing us to quantify the contribution of different variables. The PTMA was calculated about the instantaneous helical axis of tibiofemoral rotation from optical tracked kinematics. A fabricated knee model facilitated calculation optimization,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…However, while the overall scores were significantly different, the mean differences in OKS failed to exceed the “minimal important difference” threshold of five points [ 5 ] though the median score reached it. Although not validated for analysis by individual question, it is noteworthy that the largest differences were seen in the use of transport, kneeling and giving way, activities which rely heavily on the isokinetic quadriceps strength and extensor efficiency of the knee, where differences between CPKA and TKA are known to exist [ 13 , 24 , 11 ]. This ties in well with the gait data, since the most significant differences are seen in early stance, during weight acceptance and mid-stance, were the quadriceps are at their most active [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, while the overall scores were significantly different, the mean differences in OKS failed to exceed the “minimal important difference” threshold of five points [ 5 ] though the median score reached it. Although not validated for analysis by individual question, it is noteworthy that the largest differences were seen in the use of transport, kneeling and giving way, activities which rely heavily on the isokinetic quadriceps strength and extensor efficiency of the knee, where differences between CPKA and TKA are known to exist [ 13 , 24 , 11 ]. This ties in well with the gait data, since the most significant differences are seen in early stance, during weight acceptance and mid-stance, were the quadriceps are at their most active [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…This scheme of equations also includes 2 knee tendons of clinical importance—the patellar and quadriceps tendons. Thus, we additionally present the equations derived from up-to-date data 12,37 to estimate patellar tendon moment arm and force (Equations 5 and 6), as a unified point of reference for future biomechanics research on the anterior knee structural complex.…”
Section: Methodsmentioning
confidence: 99%
“…For determining patellar tendon force, first, a knee angle-dependent cubic polynomial function for patellar tendon moment arms (equation 1) was derived from a recent imaging study database, which reported data from 0°(neutral) to 120°o f knee flexion (39). This polynomial was extrapolated for patellar tendon moment arms during hyperextension up to 10°a nd set moments arms in extreme knee flexion to equal of 120°when it approached a plateau (39,40). Next, the patellar tendon force was estimated by dividing the knee moment by the patellar tendon moment arm at the specific knee angle during each time instance of motion (equation 2).…”
Section: Methodsmentioning
confidence: 99%